Are two teachers better than one? Team teaching in TBL - Yang, Lishan (2020)
Teaching the medical sciences using team-based learning (TBL) is a complex task, which requires knowledge of both the subject matter and pedagogy. To deal with these increased demands on the teacher, a strategy where every TBL session is co-taught by a Content Expert and a Facilitator was implemented. Twelve classroom sessions focusing on the interaction between these groups of teachers and their contribution in class were observed. There are quantitative and qualitative differences in the nature of the questions that they ask. The findings provide insight into how effective TBL sessions arise from complementary questioning strategies from these parties.